2014
DOI: 10.3390/ma7031830
|View full text |Cite
|
Sign up to set email alerts
|

A New Epoxy-Based Layered Silicate Nanocomposite Using a Hyperbranched Polymer: Study of the Curing Reaction and Nanostructure Development

Abstract: Polymer layered silicate (PLS) nanocomposites have been prepared with diglycidyl ether of bisphenol-A (DGEBA) epoxy resin as the matrix and organically modified montmorillonite (MMT) as the clay nanofiller. Resin-clay mixtures with different clay contents (zero, two, five and 10 wt%) were cured, both isothermally andnon-isothermally, using a poly(ethyleneimine) hyperbranched polymer (HBP), the cure kinetics being monitored by differential scanning calorimetry (DSC). The nanostructure of the cured nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…This method assumes that the degree of cure at the peak temperature, T p , is the same for all heating rates, β, and the activation energy is then determined from the slope of a plot of ln(β/ T p 2 ) versus 1/ T p . The results for T p listed in Table 2 give a value of 63.3 kJ/mol for the curing reaction of the ELP system, which is in good agreement with the value that can be found from the cure of the same epoxy resin with the same HBPEI in nanocomposites systems, for the sample with no clay content and over a higher heating rate range from 10 to 20 K/min [81]. Interestingly, this value is slightly higher than the values obtained for the non-isothermal cure of the same epoxy resin in nanocomposite systems cured with a polyoxypropylene diamine, which were in the range 49 to 54 kJ/mol [76].…”
Section: Resultssupporting
confidence: 77%
“…This method assumes that the degree of cure at the peak temperature, T p , is the same for all heating rates, β, and the activation energy is then determined from the slope of a plot of ln(β/ T p 2 ) versus 1/ T p . The results for T p listed in Table 2 give a value of 63.3 kJ/mol for the curing reaction of the ELP system, which is in good agreement with the value that can be found from the cure of the same epoxy resin with the same HBPEI in nanocomposites systems, for the sample with no clay content and over a higher heating rate range from 10 to 20 K/min [81]. Interestingly, this value is slightly higher than the values obtained for the non-isothermal cure of the same epoxy resin in nanocomposite systems cured with a polyoxypropylene diamine, which were in the range 49 to 54 kJ/mol [76].…”
Section: Resultssupporting
confidence: 77%
“…These results indicate that during the modification of bentonite by silsesquioxanes, the mineral plates practically do not change in size, which results in composites with better mechanical properties. In the case of composites EPBP1IHSP3-1.5, EPBP1IHSP3-3.0, and EPBP2IHSP3-1.5, estimation of the size of the plates was not possible due to the absence of a WAXS maximum in the curve, which is characteristic for nanocomposites with an exfoliated structure [54,55]. …”
Section: Resultsmentioning
confidence: 99%
“…Small-angle X-ray scattering studies revealed the exfoliation of MMT in the matrix. The authors of [74] used hyperbranched polyethylenimine with end amino groups as a curing agent and attained effective exfoliation. A comparison of three systems, such as triglycidyl-p-aminophenol + DDS, BADGE + poly(ester diamine), and BADGE + hyperbranched polyethylenimine, showed [75] that the exfoliation ability of MMT decreases in the mentioned sequence.…”
Section: Mineralsmentioning
confidence: 99%